1980
DOI: 10.1029/ja085ia13p08167
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the flux of sunlight in the atmosphere of Venus

Abstract: The solar flux radiometer (LSFR) aboard the Pioneer Venus (PV) sounder probe measured the intensity of sunlight in five directions to the vertical using narrow angular fields of view. The measurements in a narrow spectral channel (0.59–0.67 µm) and two broad channels (0.4–1.0 and 0.4–1.8 µm) were reduced to yield the profiles of upward and downward solar flux with a vertical resolution of 100–500 m. All the flux profiles show three distinct cloud layers with bottoms at altitudes of 57.5, 49.7, and 47.9 km. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 18 publications
5
97
0
Order By: Relevance
“…In addition, these other absorbers must explain the phase angle dependence of the uV dark markings as well as their short lifetime above the clouds (from hours to days, see Esposito et al [1983]). They must also be consistent with the visible-wavelength solar flux observations of Tomasko et al [1980] which show absorption at 58-62 km, and little absorption below. near uV solar flux absorption results from VEnErA 14 [Ekonomov et al, 1983;1984] provide an additional constraint.…”
Section: Unidentified Uv and Blue Absorptionsupporting
confidence: 63%
“…In addition, these other absorbers must explain the phase angle dependence of the uV dark markings as well as their short lifetime above the clouds (from hours to days, see Esposito et al [1983]). They must also be consistent with the visible-wavelength solar flux observations of Tomasko et al [1980] which show absorption at 58-62 km, and little absorption below. near uV solar flux absorption results from VEnErA 14 [Ekonomov et al, 1983;1984] provide an additional constraint.…”
Section: Unidentified Uv and Blue Absorptionsupporting
confidence: 63%
“…Several comprehensive radiative transfer models consistent with the data were developed at that time (Tomasko et al 1980a. The authors calculated the global balance of radiative energy and solar heating rates in the atmosphere.…”
Section: Global Radiative Energy Balancementioning
confidence: 99%
“…The measurements of the vertical profiles of downward solar fluxes by the Venera and Pioneer-Venus descent probes showed that UV and blue radiation are strongly absorbed in the upper cloud layer above 57 km. To find the global mean net solar flux, numerical models must be used to extend the spectral and spatial coverage provided by the experimental results (Tomasko et al 1980a;. The measurements and subsequent radiative transfer modeling revealed two regions where deposition of the solar energy is significant.…”
Section: Radiation Field Inside the Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…The heating rate is almost equal to that used in YT in the cloud layer, but the value is small about onesixth below the cloud layer, because YT's heating rate is too large for the real Venus near the ground. The real heating rate is estimated as about 3.0 × 10 −3 K day −1 at 0−10 km altitude, and the heating rate provided in this study is, nonetheless, too high for the real Venus near the ground (Tomasko et al 1980). Figure 2 shows the reference temperature T 0 (z), which is based on an observed value (Seiff et al 1980).…”
Section: Modelmentioning
confidence: 99%